ANALISIS QUALITY OF SERVICE PADA SISTEM MONITORING KULKAS DUA PINTU MENGGUNAKAN KAMERA USBWEBCAM BERBASIS ANDROID - sindung sasono (PSTE UNIMUS, 2023)
The high level of public consumption in the field of technology encourages innovations made in the refrigerator so that it can be monitored remotely. This study aims to monitor the inside of the refrigerator by streaming and with color video quality and measuring network performance from the motion application on the Raspberry pi to the client. This system uses one camera usbwebcam and one lamp with an input voltage of 5 volts DC connected to the Raspberry Pi 3B. The software used to configure the camera is motion while controlling the lights uses the php language stored in the Raspberry Pi 3B. The application on Android has a display of both camera data, buttons light control, and graphical information from the MQ135, MQ136, and MQ137 sensors. Network quality based on 4 QoS parameters, namely throughput, delay, jitter, and packet loss in 3 conditions can be categorized as good based on the TIPHON standard. Thevalue is throughput 119kbps to 200kbps, thevalue is delay 25.56ms to 39.26ms, thevalue is jitter 50.36ms to 77.46ms and the packet loss value is 0% to 11.1%. Thevalues are throughput, delay, and jitter affected by the light captured by the camera, while packet loss is not affected by light and temperature in the refrigerator.